2017
DOI: 10.1152/ajpheart.00822.2016
|View full text |Cite
|
Sign up to set email alerts
|

Increased activity of the orexin system in the paraventricular nucleus contributes to salt-sensitive hypertension

Abstract: The orexin system is involved in arginine vasopressin (AVP) regulation, and its overactivation has been implicated in hypertension. However, its role in salt-sensitive hypertension (SSHTN) is unknown. Here, we tested the hypothesis that hyperactivity of the orexin system in the paraventricular nucleus (PVN) contributes to SSHTN via enhancing AVP signaling. Eight-week-old male Dahl salt-sensitive (Dahl S) and age- and sex-matched Sprague-Dawley (SD) rats were placed on a high-salt (HS; 8% NaCl) or normal-salt (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
40
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 56 publications
2
40
0
Order By: Relevance
“…Our immunostaining studies showed that OX1R is expressed in the RVLM‐projecting PVN neurons indicating the potential role of OX1R in SNA outflow control. Surprisingly, there is no OX2R in the RVLM‐projecting PVN neurons although weak OX2R immunofluorescence is observed, and real‐time PCR demonstrated OX2R mRNA presence in the PVN . Instead, OX2R is highly expressed in submedius thalamic nucleus and mediodorsal thalamic nucleus.…”
Section: Discussionmentioning
confidence: 98%
See 4 more Smart Citations
“…Our immunostaining studies showed that OX1R is expressed in the RVLM‐projecting PVN neurons indicating the potential role of OX1R in SNA outflow control. Surprisingly, there is no OX2R in the RVLM‐projecting PVN neurons although weak OX2R immunofluorescence is observed, and real‐time PCR demonstrated OX2R mRNA presence in the PVN . Instead, OX2R is highly expressed in submedius thalamic nucleus and mediodorsal thalamic nucleus.…”
Section: Discussionmentioning
confidence: 98%
“…For example, loss of orexin function results in the sleep disorder narcolepsy, and increased CSF orexin levels are found in patients with increased anxiety and panic associated symptoms and in rats at a stress state . Recent studies indicate that brain orexin system is also involved in the regulation of blood pressure and SNA, and its hyperactivity in the brain is associated with hypertension . Thus, the objectives of this study are to investigate whether the PVN orexin signalling is involved in regulating SNA.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations